Trends in Islamic Education Quality Research: A Bibliometric Analysis of Scopus-Indexed Publications - Haya Adzra Afaf; Shobah Shofariyani Iryanti (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Abstract This study aims to map the trends, key contributors, collaborations, and dominant themes in research on the quality of Islamic education indexed in the Scopus database during the 2015–2025 period. Using a quantitative approach with a bibliometric design, this research analyzed 427 scientific articles through VOSviewer and Biblioshiny for R to identify publication trends, author productivity, institutional and national contributions, and the most influential keywords. The findings reveal a significant increase in publication numbers since 2019, peaking in 2024. Indonesia and Malaysia emerged as the leading contributors, with Maulana Malik Ibrahim State Islamic University of Malang identified as the most productive institution. Thematic mapping showed five major clusters: quality management, Islamic curriculum, values and character formation, social dimensions, and global education evaluation. Although international collaboration is developing, research networks remain concentrated in Southeast Asia. These results highlight the importance of strengthening international partnerships, integrating multidisciplinary approaches, and exploring emerging themes such as digitalization and Islamic financial education to enhance the global development of Islamic education quality. Keywords: Bibliometric analysis, islamic education qualit, publication trends, research collaboration, Scopus